Silicone rubber and preparation method thereof

By constructing a covalent network of vinyl silicone rubber raw rubber and an ionic network of zinc acrylate and silicon carbide nanowires in silicone rubber, the overflow of silicone rubber is suppressed and the self-healing performance is improved, which solves the problems of overflow and insufficient toughness in the preparation process and improves the mechanical properties.

CN120818244AActive Publication Date: 2025-10-21MIDGOLD SILICONE (YICHANG) CO LTD

Patent Information

Application Number
CN202510989689.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-10-21
Estimated Expiration
2045-07-17

AI Technical Summary

Technical Problem

Silicone rubber is prone to overflow during the preparation process, lacks toughness, has poor self-healing effect, and has low tensile strength, making it difficult to meet high-load application requirements.

Method used

A covalent network mainly composed of vinyl silicone rubber is combined with an ionic network composed of zinc acrylate and silicon carbide nanowires. The reversible ionic bond between Zn2+ and carboxylate is dissociated under shear force during the injection stage to achieve viscosity reduction and rapid recovery, prevent glue overflow, and enhance self-healing performance.

Benefits of technology

It effectively solves the problem of glue overflow, improves the fluidity and self-repairing ability of silicone rubber, enhances mechanical properties, and ensures good mold filling and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818244A_ABST
    Figure CN120818244A_ABST
Patent Text Reader

Abstract

The invention discloses silicone rubber and a preparation method thereof, and belongs to the technical field of silicone rubber, and the silicone rubber is prepared from the following raw materials: raw vinyl silicone rubber, zinc acrylate, a platinum catalyst, a hydrogen-containing silicone oil cross-linking agent and silicon carbide nanowires. According to the invention, a covalent network based on raw vinyl silicone rubber is constructed in the silicone rubber, and zinc acrylate and silicon carbide nanowires form an ionic network, so that the double-network structure not only can improve the technical problem of high probability of rubber overflow in the preparation process of the silicone rubber, but also can enable the silicone rubber to obtain better mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicone rubber, and in particular to silicone rubber and a preparation method thereof. Background Art

[0002] As a high-performance elastomer, silicone rubber is widely used in the medical, electronic, and automotive fields, but its preparation process often faces technical problems such as glue overflow, insufficient toughness, and poor self-healing effect. For example, the low viscosity of unvulcanized silicone rubber makes it very easy to overflow from the mold parting surface during the injection and molding process. Traditional processes can inhibit flow by adding excessive amounts of silica, but this will significantly reduce the flexibility of the material. Secondly, the Si-O bond energy of the silicone rubber main chain is low, and there is a lack of an effective energy dissipation mechanism, resulting in low tensile strength, which is difficult to meet the needs of high-load applications. In addition, the covalent cross-linking network of traditional silicone rubber is irreversible, and it is difficult to achieve self-repair after damage, which seriously affects the service life of the product. Summary of the Invention

[0003] The main purpose of the present invention is to provide a silicone rubber and a preparation method thereof, so as to solve the technical problem that silicone rubber easily overflows during the preparation process.

[0004] To achieve the above object, the present invention provides a silicone rubber. The raw materials required for preparing the silicone rubber include: vinyl silicone rubber, zinc acrylate, platinum catalyst, hydrogenated silicone oil crosslinking agent, and silicon carbide nanowires.

[0005] In some embodiments of the present invention, the mass content of vinyl in the vinyl silicone rubber is 0.8% to 1.2%.

[0006] In some embodiments of the present invention, the purity of the zinc acrylate is ≥99% and the average particle size is ≤5 μm.

[0007] In some embodiments of the present invention, the Pt content in the platinum catalyst is 3000 ppm to 5000 ppm.

[0008] In some embodiments of the present invention, the mass content of hydrogen in the hydrogen-containing silicone oil crosslinking agent is 0.8% to 1.2%.

[0009] In some embodiments of the present invention, the average diameter of the silicon carbide nanowires is 20 nm to 50 nm.

[0010] In some embodiments of the present invention, the aspect ratio of the silicon carbide nanowires is in the range of 50 to 70; and / or the specific surface area of ​​the silicon carbide nanowires is 150 m 2 / g~300 m 2 / g.

[0011] In some embodiments of the present invention, the raw materials required for preparing the silicone rubber further include aramid nanofibers and polyimide nanofibers.

[0012] In some embodiments of the present invention, the raw materials required for preparing the silicone rubber include, by weight: 100 parts of vinyl silicone rubber, 3 to 5 parts of zinc acrylate, 0.5 to 1.5 parts of platinum catalyst, 2 to 3 parts of hydrogenated silicone oil crosslinking agent, and 1 to 2 parts of silicon carbide nanowires.

[0013] The present invention also provides a method for preparing the silicone rubber as described above, comprising the following steps: S10, mixing zinc acrylate and an organic solvent, ball milling, and vacuum drying to remove the organic solvent to obtain pretreated zinc acrylate; S20, adding vinyl silicone rubber and silicon carbide nanowires into an internal mixer and mixing them for the first time, then adding the pretreated zinc acrylate and mixing them for the second time, and then adding a hydrogenated silicone oil crosslinking agent and mixing them for the third time to obtain a rubber compound; S30, injecting the rubber material and the platinum catalyst into a twin-screw extruder, mixing, extruding, injecting into a mold, and vulcanizing and molding to obtain silicone rubber.

[0014] In some embodiments of the present invention, in step S30, the vulcanization molding process includes a first vulcanization molding stage and a second vulcanization molding stage, the temperature of the first vulcanization molding stage is 90°C~110°C, and the temperature of the second vulcanization molding stage is 150°C~180°C.

[0015] The beneficial effects that can be achieved by the present invention are: The present invention constructs a covalent network based on vinyl silicone rubber in silicone rubber, and an ionic network composed of zinc acrylate and silicon carbide nanowires. The double network structure can improve the mechanical properties of silicone rubber. Moreover, the ionic network based on zinc acrylate is a reversible ionic network. Under the influence of shear force in the injection stage, the Zn in the rubber is 2+ The ionic bond with the carboxylate will dissociate briefly, resulting in a decrease in viscosity, which shows better fluidity, thus ensuring good mold filling. When the injection is stopped, that is, in a static state, the Zn in the rubber 2+It can re-coordinate with the carboxylate in a short time, so that the viscosity of the rubber can be instantly restored to a value close to the initial value or the initial value, thereby effectively locking the flow of the rubber, solving the problem of easy glue overflow in the preparation of silicone rubber from the root, and enhancing the self-healing effect of silicone rubber. Furthermore, the present invention compounds zinc acrylate and silicon carbide nanowires. The addition of silicon carbide nanowires can enhance the stability and conductivity of the ion network structure, so that the viscosity of the rubber can be quickly restored to the initial value or close to the initial value after injection shearing, locking the flow of the rubber in a very short time, further preventing the occurrence of glue overflow, and further enhancing the self-healing performance of silicone rubber. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0017] Figure 1 The present invention is a schematic flow chart of a method for preparing silicone rubber. DETAILED DESCRIPTION

[0018] It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0019] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0020] In this disclosure, terms such as "first," "second," and so on are for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, features designated as "first" or "second" may explicitly or implicitly include at least one such feature. Furthermore, the technical solutions of various embodiments may be combined, but only if they are achievable by persons of ordinary skill in the art. If a combination of technical solutions contradicts or is unachievable, such combination shall be deemed non-existent and outside the scope of protection claimed by this disclosure.

[0021] The invention provides a silicone rubber. Components required for preparing the silicone rubber include: vinyl silicone rubber raw rubber, zinc acrylate, platinum catalyst, hydrogen-containing silicone oil crosslinking agent, and silicon carbide nanowires.

[0022] In the present invention, vinyl silicone rubber raw rubber serves as the main network structure of silicone rubber, zinc acrylate serves as the dynamic ionic crosslinking point, and the platinum catalyst can catalyze the covalent crosslinking of Si-H and vinyl. The hydrogenated silicone oil crosslinking agent helps to realize the construction of the covalent crosslinking network. Silicon carbide nanowires can enhance the conduction of the ionic network, so that the viscosity of the rubber material can be quickly recovered after injection shearing, locking the flow of the rubber material, further preventing the occurrence of glue overflow, and improving the mechanical strength of the silicone rubber.

[0023] The present invention constructs a covalent network based on vinyl silicone rubber in silicone rubber, and an ionic network composed of zinc acrylate and silicon carbide nanowires. The double network structure can improve the mechanical properties of silicone rubber. Moreover, the ionic network based on zinc acrylate is a reversible ionic network. Under the influence of shear force in the injection stage, the Zn in the rubber is 2+ The ionic bond with the carboxylate will dissociate briefly, resulting in a decrease in viscosity, which shows better fluidity, thus ensuring good mold filling. When the injection is stopped, that is, in a static state, the Zn in the rubber 2+ It can re-coordinate with the carboxylate in a short time, so that the viscosity of the rubber can be instantly restored to a value close to the initial value or the initial value, thereby effectively locking the flow of the rubber, solving the problem of easy glue overflow in the preparation of silicone rubber from the root, and enhancing the self-healing effect of silicone rubber. Furthermore, the present invention compounds zinc acrylate and silicon carbide nanowires. The addition of silicon carbide nanowires can enhance the stability and conductivity of the ion network structure, so that the viscosity of the rubber can be quickly restored to the initial value or close to the initial value after injection shearing, locking the flow of the rubber in a very short time, further preventing the occurrence of glue overflow, and further enhancing the self-healing performance of silicone rubber.

[0024] In some embodiments, the molecular weight of the vinyl silicone rubber is 600,000 to 800,000, and the mass content of vinyl in the vinyl silicone rubber is 0.8% to 1.2%, which helps the silicone rubber build a stable covalent network.

[0025] In some embodiments, the purity of zinc acrylate is greater than or equal to 99%, and the average particle size is ≤5 μm. For example, the average particle size may be 1 μm to 5 μm.

[0026] In some embodiments, the mass content of Pt in the platinum catalyst is 3000 ppm to 5000 ppm, which can promote the construction of a covalent network.

[0027] In some embodiments, the mass content of hydrogen in the hydrogenated silicone oil crosslinker is 0.8% to 1.2%, which can promote the construction of a covalent network.

[0028] In some embodiments, the average diameter of the silicon carbide nanowires is 20 nm to 50 nm, which can be 20 nm, 30 nm, 40 nm, 50 nm, etc., which can increase the contact area between the silicon carbide nanowires and other raw materials, promote the construction of the ion network, form a silicon carbide nanowire-ion cluster network, strengthen the rapid coordination between ions, inhibit the overflow phenomenon, and improve the mechanical properties of silicone rubber and increase the tensile modulus of silicone rubber.

[0029] In some embodiments, the aspect ratio of silicon carbide nanowires is in the range of 50 to 70, which is beneficial to enhance ion network conduction, strengthen rapid coordination between ions, inhibit glue overflow, and improve the mechanical properties of silicone rubber and increase the tensile modulus of silicone rubber.

[0030] In some embodiments, the specific surface area of ​​the silicon carbide nanowires is 150 m 2 / g~300 m 2 / g, and having a large specific surface area is beneficial to enhancing the ion network conduction, strengthening the rapid coordination between ions, inhibiting the overflow phenomenon, and also improving the mechanical properties of silicone rubber and increasing the tensile modulus of silicone rubber.

[0031] In some embodiments, the raw materials for preparing silicone rubber include the following components, calculated by weight: 100 parts of vinyl silicone rubber, 3 to 5 parts of zinc acrylate, 0.5 to 1.5 parts of platinum catalyst, 2 to 3 parts of hydrogenated silicone oil crosslinking agent, and 1 to 2 parts of silicon carbide nanowires.

[0032] In some embodiments, the raw materials for preparing silicone rubber include the following components, calculated by weight: 100 parts of vinyl silicone rubber, 3.5 parts of zinc acrylate, 0.8 parts of platinum catalyst, 2.2 parts of hydrogenated silicone oil crosslinking agent, and 1.5 parts of silicon carbide nanowires.

[0033] In some embodiments, the raw materials of silicone rubber also include aramid nanofibers and polyimide microfibers. The addition of nano- and micro-scale fibers can fill molecular defects in silicone rubber, prevent the expansion of microcracks, and further improve the mechanical properties of silicone rubber.

[0034] In some embodiments, the diameter of the aramid nanofiber is in the range of 5 nm to 10 nm, and the aspect ratio is ≥1000; the diameter of the polyimide nanofiber is in the range of 1 μm to 2 μm, and the length is in the range of 50 μm to 100 μm.

[0035] In some embodiments, calculated by weight, based on 100 parts of vinyl silicone rubber, the added amount of aramid nanofiber is 0.5-1.2 parts, and the added amount of polyimide microfiber is 0.8-1.5 parts.

[0036] The present invention also provides a method for preparing silicone rubber, referring to Figure 1 , including the following steps: S10, mixing zinc acrylate and an organic solvent, ball milling, and vacuum drying to remove the organic solvent to obtain pretreated zinc acrylate; S20, adding vinyl silicone rubber and silicon carbide nanowires into an internal mixer and mixing them for the first time, then adding the pretreated zinc acrylate from step S10 and mixing them for the second time, then adding a hydrogenated silicone oil crosslinking agent and mixing them for the third time to obtain a rubber compound; S30, injecting the rubber material and the platinum catalyst into a twin-screw extruder, mixing, extruding, injecting into a mold, and vulcanizing and molding to obtain silicone rubber.

[0037] In the present invention, step S10 pre-treats zinc acrylate to obtain nano-scale zinc acrylate, so that the average particle size of the nano-scale zinc acrylate is less than or equal to 20 nm, which can increase the Zn 2+ exposure, which is beneficial to obtain Zn 2+ The ion clusters formed with carboxylates increase the Zn 2+ It can also improve the dispersion of zinc acrylate in the rubber compound and facilitate the construction of an ionic network in the silicone rubber.

[0038] In some embodiments, the balls used in the ball milling process are zirconia balls. The collision of the zirconia balls can generate local high temperatures greater than or equal to 200°C, which can increase the crystal defects in zinc acrylate and increase the surface energy of zinc acrylate, thereby improving the interfacial bonding strength between zinc acrylate and silicone rubber, and zinc acrylate and silicon carbide nanowires, thereby improving the mechanical properties of silicone rubber and increasing the tensile strength.

[0039] In some embodiments, the organic solvent includes anhydrous ethanol. The ethanol molecules in anhydrous ethanol can be inserted into the lattice layers of zinc acrylate to assist in deagglomeration and prevent agglomeration. They can also be adsorbed onto the surface of zinc acrylate to prevent zinc acrylate particles from agglomerating, thereby improving the dispersibility of zinc acrylate.

[0040] In some embodiments, the mass ratio of zinc acrylate to the organic solvent is 1:3 to 1:5.

[0041] In some embodiments, the ball milling time is 2 h to 3 h, and the ball milling speed is 300 rpm to 500 rpm.

[0042] In step S10 , the purpose of vacuum drying is to remove the residual organic solvent. In some embodiments, vacuum drying can be performed at 60° C. to 70° C. to remove the residual organic solvent.

[0043] In some embodiments, the temperature of the first mixing in step S20 is 40° C. to 50° C., and the mixing time is 5 min to 10 min.

[0044] In some embodiments, the temperature of the second mixing in step S20 is 75° C. to 85° C., and the mixing time is 20 min to 30 min.

[0045] In some embodiments, the temperature of the third mixing in step S20 is 100° C. to 105° C., and the time is 5 min to 10 min.

[0046] In some embodiments, at least one of aramid nanofibers and polyimide microfibers is further added in step S20.

[0047] In some embodiments, aramid nanofibers are added during the initial mixing process. Specifically, the aramid nanofibers are dispersed in a mixed solution of DMSO and KOH to form an aramid nanofiber suspension. The aramid nanofiber suspension is preheated to 40°C to 45°C. The preheated aramid nanofiber suspension, vinyl silicone rubber, and silicon carbide nanowires are then added to an internal mixer, followed by the initial mixing process. Preheating the aramid nanofiber suspension helps reduce its viscosity and enhances uniform mixing with the vinyl silicone rubber and silicon carbide nanowires.

[0048] In some embodiments, the mass ratio of DMSO to KOH is 95:5.

[0049] In some embodiments, the mass ratio of aramid nanofibers to a mixed solution of DMSO and KOH is (2-3):100. Under the above ratio conditions, not only can the concentration of the fibers be prevented from being too low, which increases the distance between the fibers and results in insufficient improvement in the mechanical properties of the silicone rubber, but also the viscosity of the rubber compound can be prevented from being too high due to the formation of a three-dimensional network structure caused by an excessively high concentration.

[0050] In some embodiments, the polyimide micron fiber is added during the second mixing. Specifically, after the first mixing is completed, the pretreated zinc acrylate is added, and the polyimide micron fiber is simultaneously added for the second mixing.

[0051] In some embodiments, the extrusion temperature is 80°C to 90°C, and the shear rate is 100s -1 ~120s -1 .

[0052] In some embodiments, the vulcanization molding temperature is 90°C to 180°C.

[0053] In some embodiments, the vulcanization molding includes a first vulcanization molding stage and a second vulcanization molding stage.

[0054] In some embodiments, the temperature of the first vulcanization molding is 90°C to 110°C, and the temperature of the second vulcanization molding is 150°C to 180°C. In the first vulcanization molding stage, Zn 2+ It can quickly coordinate with carboxylate groups to form a dynamic and reversible ion cross-linking network, which can instantly increase the structural viscosity of the rubber and give the rubber the characteristics of "shear thinning-fast recovery". After injection, the viscosity of the rubber can be restored to the initial state or close to the initial state in a short time. In the second vulcanization molding stage, the platinum catalyst can promote the Si-H and vinyl addition reaction, build a covalent network, and wrap Zn 2+ and carboxylates to form ion clusters, limiting Zn 2+ In this embodiment, the double-curing process to build a basic covalent network and an ionic network not only solves the problem of silicone rubber overflow, but also improves the mechanical properties of silicone rubber.

[0055] The technical solutions of the present invention are further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention and are not used to limit the present invention.

[0056] Example 1 Example 1 The steps for preparing silicone rubber are as follows: S10. Mix zinc acrylate and anhydrous ethanol as an organic solvent according to the weight parts in Table 1, with a mass ratio of zinc acrylate to anhydrous ethanol being 1:3. Use zirconium oxide balls as ball milling tools, the ball milling speed is 400 rpm, and the ball milling is carried out for 2 hours. Then, vacuum drying is carried out at 60° C. to remove residual anhydrous ethanol to obtain pretreated zinc acrylate, wherein the average particle size of the pretreated zinc acrylate is less than or equal to 20 nm.

[0057] S20, adding vinyl silicone rubber and silicon carbide nanowires in parts by weight according to Table 1 to an internal mixer, performing a first mixing at 45° C. for 5 min, then adding the pretreated zinc acrylate described in step S10, performing a second mixing at 85° C. for 20 min, then adding the hydrogenated silicone oil crosslinking agent, and performing a third mixing at 100° C. for 8 min to obtain a rubber compound, wherein the molecular weight of the vinyl silicone rubber is 800,000, and the specific surface area of ​​the silicon carbide nanowire is 200 m 2 / g, the aspect ratio is 70, the average diameter is 50nm, the mass content of vinyl is 1.0%, the purity of zinc acrylate is greater than or equal to 99%, the average particle size is 1μm, and the mass content of hydrogen in the hydrogen-containing silicone oil is 1.0%.

[0058] S30, inject the rubber compound and platinum catalyst into the twin-screw extruder, mix, and heat at 80℃ for 100s. -1The silicone rubber was extruded and injected into the mold at a shear rate of 10000. The first vulcanization molding was carried out at 90°C for 10 minutes in the mold, and then the second vulcanization molding was carried out at 160°C for 10 minutes to obtain the silicone rubber.

[0059] Example 2 Example 2 Silicone rubber was prepared by referring to the steps of Example 1, except that the weight parts of the raw materials in Example 2 were different, as shown in Table 1.

[0060] Example 3 Example 3 Silicone rubber was prepared by referring to the steps of Example 1, except that the weight parts of the raw materials in Example 3 were different, as shown in Table 1.

[0061] Example 4 Example 4 Silicone rubber was prepared by referring to the steps of Example 1, except that the weight parts of the raw materials in Example 4 were different, as shown in Table 1.

[0062] Example 5 Example 5 Silicone rubber was prepared by referring to the steps of Example 1, except that the weight parts of the raw materials in Example 5 were different, as shown in Table 1.

[0063] Example 6 Example 6 Silicone rubber was prepared by referring to the steps of Example 1, except that in step S10 of Example 6, the mass ratio of zinc acrylate to anhydrous ethanol was controlled to be 1:5.

[0064] Example 7 Example 7 Silicone rubber was prepared by referring to the steps of Example 1, except that in step S20 of Example 7, the temperature of the first mixing was 70°C.

[0065] Example 8 Example 8 Silicone rubber was prepared by referring to the steps of Example 1, except that in step S20 of Example 8, the temperature of the second mixing was 70°C.

[0066] Example 9 Example 9 prepared silicone rubber by referring to the steps of Example 1, except that in step S20 of Example 9, the temperature of the third mixing was 70°C.

[0067] Example 10 Example 10: Silicone rubber was prepared by referring to the steps of Example 1, except that, in step S30 of Example 10, the temperature of the first vulcanization molding was 100°C.

[0068] Example 11 Example 11: Silicone rubber was prepared by referring to the steps of Example 1, except that, in step S30 of Example 11, the temperature of the second vulcanization molding was 150°C.

[0069] Example 12 Example 12: Silicone rubber was prepared by referring to the steps of Example 1, except that in step S30, the shear rate was 120s -1 .

[0070] Example 13 Example 13 prepared silicone rubber with reference to the steps of Example 1, except that, in step S20 of Example 13, 1 part of aramid nanofiber and 1.5 parts of polyimide micron fiber were added, the diameter of the aramid nanofiber was 10 nm, the aspect ratio was 1500, and the diameter range of the polyimide nanofiber was 2 μm and the length was 50 μm.

[0071] Step S20 is as follows: dispersing aramid nanofibers into a mixed solution of DMSO and KOH (mass ratio 95:5) to obtain an aramid nanofiber suspension, wherein the mass ratio of aramid nanofibers to the mixed solution in the aramid nanofiber suspension is 2:100, preheating the aramid nanofiber suspension to 45°C, adding vinyl silicone rubber and silicon carbide nanowires in accordance with the weight parts in Table 1 in an internal mixer, performing a first mixing at 45°C for 5 minutes, then adding the pretreated zinc acrylate and polyimide micron fibers described in step S10, performing a second mixing at 85°C for 30 minutes, then adding the hydrogenated silicone oil crosslinking agent, and performing a third mixing at 100°C for 8 minutes to obtain a rubber compound, wherein the molecular weight of the vinyl silicone rubber is 800,000, and the specific surface area of ​​the silicon carbide nanowire is 200 m 2 / g, the aspect ratio is 70, the average diameter is 50nm, the mass content of vinyl is 1.0%, the purity of zinc acrylate is greater than or equal to 99%, the average particle size is 1μm, and the mass content of hydrogen in the hydrogen-containing silicone oil is 1.0%.

[0072] Comparative Example 1 Comparative Example 1: Silicone rubber was prepared by referring to the steps of Example 1, except that silicon carbide nanowires were not added to the raw material formula in Comparative Example 1.

[0073] Comparative Example 2 Comparative Example 1: Silicone rubber was prepared by referring to the steps of Example 1, except that granular silicon carbide with an average particle size of 50 nm was added in Comparative Example 2.

[0074] Comparative Example 3 Comparative Example 3: Silicone rubber was prepared by referring to the steps of Example 1, except that the zinc acrylate was not treated in step S10.

[0075] Table 1

[0076] Performance Testing Test 1, anti-glue overflow test: heat a stainless steel inclined plate with an inclination of 85° and a surface roughness of 0.8μm to 150℃±1℃ and keep the temperature constant for 30min. Collect the glue extruded into the mold of the embodiment and the comparative example through step S30 respectively, place it in an environment of 23±2℃ and 50±5%RH for 24 hours, and then apply it to the end of the stainless steel inclined plate. Start the timer, record the position where it flows to after 10min, and measure the distance from this position to the end, and take the average value of three parallel experiments.

[0077] Judgment standard: Flow distance ≤ 3mm is qualified.

[0078] Test 2, tensile strength and elongation at break test: The tensile test was carried out on a U-CANUT-2060 tensile machine. The test standard was GB / T528-2009, the test temperature was 25 ° C, the tensile speed was 500 mm / min, and the tensile strength and elongation at break were tested. The results are shown in Table 2.

[0079] Table 2

[0080] Combined with Table 1 and Table 2, the flow distances of the rubber materials prepared in Examples 1 to 13 are all within 3 mm, indicating that they have good anti-overflow performance, and also obtain good tensile strength and elongation at break, and have excellent mechanical properties. Among them, Example 13 adds aramid nanofibers and polyimide nanofibers, which not only enhances the mechanical properties of silicone rubber, but also improves the anti-overflow problem to a certain extent.

[0081] Comparative Example 1 does not add silicon carbide nanowires, Comparative Example 2 adds granular silicon carbide, and Comparative Example 3 does not pretreat zinc acrylate, all of which weaken the anti-overflow performance of the silicone rubber to a certain extent and also affect the mechanical properties.

[0082] The above are only preferred embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention description and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A silicone rubber, characterized in that: The raw materials required for preparing the silicone rubber include: vinyl silicone rubber, zinc acrylate, platinum catalyst, hydrogen-containing silicone oil crosslinking agent, and silicon carbide nanowires.

2. The silicone rubber according to claim 1, characterized in that The mass content of vinyl in the vinyl silicone rubber raw rubber is 0.8% to 1.2%.

3. The silicone rubber according to claim 1, characterized in that The purity of the zinc acrylate is ≥99% and the average particle size is ≤5 μm.

4. The silicone rubber according to claim 1, characterized in that The Pt content in the platinum catalyst is 3000ppm~5000ppm.

5. The silicone rubber according to claim 1, characterized in that The mass content of hydrogen in the hydrogen-containing silicone oil crosslinking agent is 0.8% to 1.2%.

6. The silicone rubber according to claim 1, characterized in that The average diameter of the silicon carbide nanowires is 20 nm to 50 nm; and / or the aspect ratio of the silicon carbide nanowires is in the range of 50 to 70; and / or the specific surface area of ​​the silicon carbide nanowires is 150 m 2 / g~300 m 2 / g.

7. The silicone rubber according to claim 1, characterized in that The raw materials required for preparing the silicone rubber also include aramid nanofibers and polyimide nanofibers.

8. The silicone rubber according to claim 1, wherein Calculated by weight, the raw materials required for preparing the silicone rubber include: 100 parts of vinyl silicone rubber, 3 parts to 5 parts of zinc acrylate, 0.5 parts to 1.5 parts of platinum catalyst, 2 parts to 3 parts of hydrogenated silicone oil crosslinking agent, and 1 part to 2 parts of silicon carbide nanowires.

9. A method for preparing the silicone rubber according to any one of claims 1 to 8, characterized in that: The following steps are involved: S10, mixing zinc acrylate and an organic solvent, ball milling, and vacuum drying to remove the organic solvent to obtain pretreated zinc acrylate; S20, adding vinyl silicone rubber and silicon carbide nanowires into an internal mixer and mixing them for the first time, then adding the pretreated zinc acrylate and mixing them for the second time, and then adding a hydrogenated silicone oil crosslinking agent and mixing them for the third time to obtain a rubber compound; S30, injecting the rubber material and platinum catalyst into a twin-screw extruder, mixing, extruding and injecting into a mold, and vulcanizing and molding to obtain silicone rubber.

10. The method for preparing silicone rubber according to claim 9, characterized in that: In step S30, the vulcanization molding process includes a first vulcanization molding stage and a second vulcanization molding stage. The temperature of the first vulcanization molding stage is 90°C to 110°C, and the temperature of the second vulcanization molding stage is 150°C to 180°C.

Citation Information

Patent Citations

  • Production process of zinc acrylate

    CN102351683A

  • Renewable ethylene propylene diene monomer rubber material based on reversible ionic crosslinking and preparation method thereof

    CN118725203A

  • Nano silicone rubber composite material as well as preparation method and application thereof

    CN119978821A

  • Enhanced carboxyl rubber and preparation method thereof

    CN120137328A

  • Carbon fiber composite material and method for producing thereof

    JP2016222937A

Cited By

  • Silicone rubber anti-skid material for food shoes and preparation method of silicone rubber anti-skid material

    CN122080646A

  • A food-grade silicone rubber anti-slip material for footwear and its preparation method

    CN122080646B